Electrolyte for flexibly-packaged cylindrical battery and preparation method of electrolyte

Through the combination electrolyte formula of lithium salt and a variety of carbonate organic solvents, the problems of the electrolyte in the exudate and wetting properties of the electrolyte of the soft-pack cylindrical battery are solved, the electrochemical performance and cycle life of the battery are improved, and the Low temperature performance and safety.

CN119315118AActive Publication Date: 2025-01-14广东嘉尚新能源科技有限公司

Patent Information

Application Number
CN202411286163.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-14
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

During the production process, the existing soft-pack cylindrical battery electrolyte has problems such as difficulty in exudation, poor cell wetting, low wetting efficiency, poor low temperature performance and limited cycle life. It is difficult to improve the permeability, wetting and electricity of the electrolyte at the same time. Chemical properties.

Method used

Combined electrolyte formulations using lithium salts, a variety of carbonate organic solvents and functional additives, including lithium hexafluorophosphate, lithium difluorosulfonimide, ethylene carbonate, propyl propionate, vinyl carbonate, propylene carbonate, propylene carbonate , vinyl carbonate, propylene sulfite, vinyl sulfate, fluorovinyl carbonate, lithium bisoxalate borate, lithium bisfluorooxalate borate, perfluorooctyl ammonium sulfonate and antioxidants, etc., and are de-extracted by stirring and vacuum Gas process preparation to optimize the viscosity and conductivity of the electrolyte.

Benefits of technology

It significantly improves the permeability and wetting efficiency of the electrolyte, shortens the liquid injection time of the battery, improves the electrochemical performance and cycle life of the battery, and improves the low-temperature performance and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005043162310000121
    Figure BDA0005043162310000121
  • Figure BDA0005043162310000131
    Figure BDA0005043162310000131
Patent Text Reader

Abstract

The invention discloses an electrolyte for a soft package cylindrical battery. The electrolyte comprises the following components in parts by weight: 10-25 parts of lithium salt, 60-85 parts of an organic solvent and 5-15 parts of a functional additive, the lithium salt is prepared from 10 to 18 parts of lithium hexafluorophosphate, 2 to 5 parts of lithium bis (fluorosulfonyl) imide and 0.1 to 1 part of lithium difluorophosphate; the organic solvent is prepared from 10 to 20 parts of ethylene carbonate, 30 to 45 parts of propyl propionate, 10 to 20 parts of ethylene carbonate and 5 to 10 parts of propylene carbonate; the functional additive is prepared from 0.5 to 2 parts of vinylene carbonate, 1 to 3 parts of propylene sulfite, 3 to 8 parts of ethylene sulfate, 0.5 to 1.5 parts of fluoroethylene carbonate, 0.1 to 0.5 part of lithium bis (oxalato) borate and 0.1 to 0.5 part of lithium bis (oxalato) borate. The electrolyte disclosed by the invention is applied to the soft package cylindrical battery, the permeability and infiltration efficiency of the electrolyte can be remarkably improved, and the electrochemical performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary battery preparation, and in particular relates to an electrolyte for a soft-package cylindrical battery and a preparation method thereof. Background Art

[0002] Soft-pack cylindrical batteries are widely used in portable electronic devices and electric vehicles due to their high energy density, light weight and flexibility. However, existing soft-pack cylindrical batteries face a series of technical challenges in the production process, the most prominent of which is the electrolyte penetration and infiltration problem.

[0003] Traditional soft-pack cylindrical battery electrolytes usually use carbonate solvents and lithium hexafluorophosphate (LiPF6) as the main components. Although this formula has good electrochemical properties, it has the following problems in practical applications:

[0004] 1) Difficulty in liquid penetration: Due to the high viscosity of the electrolyte, it is difficult to quickly penetrate into the internal structure of the electrode material during the injection process, resulting in prolonged injection time and affecting production efficiency.

[0005] 2) Poor wettability of battery cells: The existing electrolyte has insufficient affinity with the electrode material, making it difficult to fully wet the electrode surface and pores, resulting in "dry areas" inside the battery, affecting the battery's capacity and performance.

[0006] 3) Low wetting efficiency: The electrolyte is unevenly distributed inside the battery, and it takes a long time to achieve complete wetting, which extends the battery production cycle.

[0007] 4) Poor low-temperature performance: The viscosity of traditional electrolytes increases significantly in low-temperature environments, resulting in obstruction of lithium ion transmission, which seriously affects the low-temperature discharge performance of the battery.

[0008] 5) Limited cycle life: Existing electrolytes are prone to side reactions during long-term circulation, which leads to increased internal resistance of the battery and accelerated capacity decay, affecting the service life of the battery.

[0009] To solve the above problems, researchers have tried to add functional additives to the electrolyte, such as VC or FEC. However, these methods can only improve one aspect of performance and it is difficult to solve multiple problems such as difficult liquid penetration, poor wettability and low wetting efficiency at the same time. Therefore, the development of a new electrolyte formula and its preparation method that can comprehensively improve the performance of soft-pack cylindrical batteries has important practical significance and market value. Summary of the invention

[0010] The purpose of the present invention is to provide an electrolyte for a soft-pack cylindrical battery with excellent permeability, wettability and electrochemical properties and a preparation method thereof in view of the deficiencies of the prior art.

[0011] To achieve the above object, the present invention provides the following technical solutions:

[0012] An electrolyte for a soft-pack cylindrical battery, comprising the following components in parts by weight: 10-25 parts of a lithium salt, 60-85 parts of an organic solvent, and 5-15 parts of a functional additive;

[0013] The lithium salt includes 10-18 parts of lithium hexafluorophosphate (LiPF6), 2-5 parts of lithium bis(fluorosulfonyl)imide (LiFSI) and 0.1-1 parts of lithium difluorophosphate (LiPO2F2);

[0014] The organic solvent comprises 10-20 parts of ethylene carbonate (DMC), 30-45 parts of propyl propionate (PA), 10-20 parts of ethylene carbonate (EC) and 5-10 parts of propylene carbonate (PC);

[0015] The functional additives include 0.5-2 parts of vinylene carbonate (VC), 1-3 parts of propylene sulfite (PS), 3-8 parts of diethylene sulfate (DTD), 0.5-1.5 parts of fluoroethylene carbonate (FEC), 0.1-0.5 parts of lithium bis(oxalatoborate) (LiBOB) and 0.1-0.5 parts of lithium bis(fluorooxalatoborate) (LiDFOB).

[0016] Preferably, the viscosity of the electrolyte is 2-8 cP, and the conductivity of the electrolyte at room temperature is ≥10 mS / cm.

[0017] Preferably, the electrolyte further comprises 0.1-0.5 parts of a wetting agent, perfluorooctane sulfonate (PFSA).

[0018] Preferably, the electrolyte further comprises a wetting agent C2F5CONH(CH2CH2O) 23 COC2F50.1-0.5 parts.

[0019] Preferably, the electrolyte further comprises 0.1-0.5 parts of an antioxidant 2,6-di-tert-butyl-4-methylphenol (BHT), which prevents the electrolyte from oxidative degradation under high temperature conditions, maintains the chemical stability and conductivity of the electrolyte, and thus enhances the durability of the battery.

[0020] Preferably, the electrolyte also includes 0.5-1 part of flame retardant tris(2,2,2-trifluoroethyl)phosphate (TTFP), which can improve the flame retardant properties of the electrolyte and ensure the safety of the battery under extreme conditions such as high temperature or short circuit.

[0021] Preferably, the electrolyte further comprises 0.1-1 part of chelating additive 18-crown ether-6.

[0022] In addition, the present invention also provides a method for preparing the electrolyte for the soft-pack cylindrical battery, comprising the following steps:

[0023] (1) Weigh each component according to the formula ratio;

[0024] (2) mixing organic solvents of ethylene carbonate (DMC), propyl propionate (PA), ethylene carbonate (EC) and propylene carbonate (PC) at 20° C. to 30° C. and stirring at a speed of 500 to 1000 rpm for 10 to 30 min to fully mix them;

[0025] (3) adding functional additives vinylene carbonate (VC), propylene sulfite (PS), diethylene sulfate (DTD), fluoroethylene carbonate (FEC), lithium bis(oxalatoborate) (LiBOB) and lithium bis(fluorooxalatoborate) (LiDFOB) to the mixed solvent in sequence, and continuing to stir under the above conditions for 30-60 minutes until the additives are completely dissolved;

[0026] (4) adding lithium salts of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium difluorophosphate (LiPO2F2) to the mixed solution in multiple times, stirring at 20°C to 30°C for 15-30 minutes after each addition until the lithium salt is completely dissolved;

[0027] (5) Degas the obtained electrolyte under a vacuum condition of -0.08 to -0.1 MPa for 2 to 4 hours to make the gas content in the electrolyte ≤50 ppm.

[0028] Preferably, the entire preparation process is carried out in an inert atmosphere with a moisture content of ≤0.1 ppm and an oxygen content of ≤0.1 ppm.

[0029] Compared with the prior art, the present invention has at least the following beneficial effects:

[0030] 1) Organic solvents DMC and EC are carbonate solvents, which can provide a stable electrochemical window and excellent ion conductivity; the introduction of PA and PC as low-viscosity solvents can effectively reduce the viscosity of the electrolyte and increase the wetting speed, especially PA has excellent wettability, which can greatly improve the wetting ability of the electrolyte to the electrode material; EC and PC contain active carbonate groups, which can form a dense SEI film on the electrode surface, inhibit side reactions, and improve Coulomb efficiency; the reasonable combination of the four solvents forms a multi-solvent system, which can significantly reduce the viscosity of the electrolyte and improve the wetting performance of the electrolyte while ensuring ion conduction, while inhibiting side reactions and improving battery performance.

[0031] 2) Functional additives VC and FEC can form a stable SEI film on the electrode surface, inhibit electrolyte decomposition, and improve the initial coulombic efficiency and cycle stability; PS and DTD can optimize the composition and structure of the SEI film and further inhibit side reactions; LiBOB and LiDFOB can improve the high temperature stability and overcharge protection of the electrolyte. This combination of functional additives can optimize electrolyte performance from different angles and improve the cycle life and safety performance of the battery.

[0032] 3) The use of a combination of multiple lithium salts, LiPF6, LiFSI and LiPO2F2, can give full play to their respective advantages and synergistically improve the performance of the electrolyte; among them, LiPF6 has high conductivity and can increase the battery rate; LiFSI can form a stable passivation layer on the aluminum current collector, inhibit corrosion, and increase the battery cycle life; LiPO2F2 can improve the thermal stability of the electrolyte. The optimized combination of the three lithium salts can ensure high conductivity while taking into account the battery's cycle performance and safety performance.

[0033] In summary, the electrolyte of the present invention is applied to soft-pack cylindrical batteries, which can significantly improve the permeability and wetting efficiency of the electrolyte, shorten the battery injection time, and improve the electrochemical performance of the battery. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In the first aspect of the present application, the present application provides an electrolyte for a soft-pack cylindrical battery, comprising the following components in parts by weight: 10-25 parts of a lithium salt, 60-85 parts of an organic solvent, and 5-15 parts of a functional additive;

[0036] The lithium salt includes 10-18 parts of lithium hexafluorophosphate (LiPF6), 2-5 parts of lithium bis(fluorosulfonyl)imide (LiFSI) and 0.1-1 parts of lithium difluorophosphate (LiPO2F2);

[0037] The organic solvent includes 10-20 parts of ethylene carbonate (DMC), 30-45 parts of propyl propionate (PA), 10-20 parts of ethylene carbonate (EC) and 5-10 parts of propylene carbonate (PC);

[0038] The functional additives include 0.5-2 parts of vinylene carbonate (VC), 1-3 parts of propylene sulfite (PS), 3-8 parts of diethyl sulfate (DTD), 0.5-1.5 parts of fluoroethylene carbonate (FEC), 0.1-0.5 parts of lithium bis(oxalatoborate) (LiBOB) and 0.1-0.5 parts of lithium bis(fluorooxalatoborate) (LiDFOB).

[0039] In one embodiment of the present application, the viscosity of the electrolyte is 2-8cP, and the conductivity of the electrolyte at room temperature is ≥10mS / cm. It can be ensured that the electrolyte has excellent ion conductivity and low viscous resistance. Low viscosity is conducive to the rapid infiltration of the electrolyte into the electrode pores, and high conductivity reduces the interface impedance and increases the number of lithium ion migration. The synergistic effect of the two not only speeds up the formation speed of the battery and shortens the production line time, but also improves the battery rate performance and reduces the internal resistance, which is particularly suitable for large current charging and discharging.

[0040] In one embodiment of the present application, the electrolyte further includes 0.1-0.5 parts of a wetting agent, perfluorooctane sulfonate (PFSA), which can reduce the surface tension of the electrolyte, promote the uniform diffusion of the electrolyte on the electrode surface, and improve the wettability of the electrolyte to the electrode material.

[0041] In one embodiment of the present application, the electrolyte further includes a wetting agent C2F5CONH(CH2CH2O) 23 COC2F50.1-0.5 parts. It can reduce the surface tension of the electrolyte, improve the wettability of the electrolyte, make the electrolyte more evenly distributed on the electrode surface, and improve the charge and discharge efficiency of the battery; and the wetting agent has the ability to increase the dissociation degree of lithium salt, thereby further improving the conductivity of the electrolyte and reducing the battery impedance. Among them, C2F5CONH (CH2CH2O) 23 COC2F5 is 3% fully halogenated amide polyoxyethylene ester.

[0042] In one embodiment of the present application, the electrolyte further comprises 0.1-0.5 parts of a wetting agent, perfluorooctane sulfonate (PFSA) and C2F5CONH (CH2CH2O). 23 COC2F5 0.1-0.5 parts. The fluorine-containing group can reduce the surface tension of the electrolyte, and the polyether chain is hydrophilic. The two work together to greatly improve the wettability of the electrolyte and accelerate the penetration rate of the electrolyte in the electrode pores, especially for the lyophobic diaphragm and electrode, the wetting effect is more significant.

[0043] Therefore, the synergistic effect of the two wetting agents can significantly reduce the surface tension of the electrolyte and improve the wetting and spreading of the electrolyte on the diaphragm and electrode; at the same time, the ether bonds in the wetting agent molecules have certain film-forming properties, which can form a uniform and dense wetting layer on the electrode surface, repair the areas with poor electrode wettability, and improve the utilization rate of the electrode. In addition, while improving the wettability, the two wetting agents have little effect on the viscosity of the electrolyte, maintaining the low viscosity characteristics of the electrolyte, and can form a synergistic effect with the above-mentioned low-viscosity compound solvent.

[0044] In one embodiment of the present application, the electrolyte further includes 0.1-0.5 parts of antioxidant 2,6-di-tert-butyl-4-methylphenol (BHT). It can effectively remove peroxides and free radicals in the electrolyte, inhibit the oxidative degradation of the electrolyte, and improve the storage life of the battery; the phenolic hydroxyl group in the BHT molecule can react with the peroxide to form a stable quinone structure, thereby interrupting the oxidation chain reaction; at the same time, the BHT molecule can also form a dense passivation layer on the electrode surface, reducing the direct contact between the electrolyte and the electrode, and further inhibiting the occurrence of side reactions. Therefore, adding BHT can greatly improve the high-temperature storage performance and self-discharge characteristics of the battery.

[0045] In one embodiment of the present application, the electrolyte further includes 0.5-1 part of the flame retardant tris(2,2,2-trifluoroethyl)phosphate (TTFP). The introduction of the flame retardant TTFP can give the electrolyte good flame retardant properties and improve the thermal stability and safety of the battery. When the battery temperature rises abnormally, the TTFP molecules will preferentially undergo an endothermic decomposition reaction to cool the battery and delay the thermal runaway process; at the same time, the phosphoric acid produced by the decomposition of TTFP forms a high-temperature resistant Li3PO4 precipitate with the lithium salt, forming a dense ceramic coating on the surface of the diaphragm, blocking the direct contact between the positive and negative electrodes, and inhibiting the further deterioration of thermal runaway, thereby greatly increasing the thermal runaway temperature and thermal stability time of the battery, and reducing the potential safety hazards of the battery.

[0046] In one embodiment of the present application, the electrolyte further includes 0.1-1 part of the chelating additive 18-crown ether-6. The addition of the chelating agent 18-crown ether-6 can effectively chelate free metal ion impurities in the electrolyte, especially transition metal ions such as Fe and Ni; the ether oxygen atoms in the 18-crown ether-6 molecule form coordination bonds with the metal ions, wrapping them in the center of the ring structure, effectively inhibiting the deposition of metal ions on the electrode surface, reducing the active sites of the catalytic decomposition of the electrolyte, thereby improving the coulombic efficiency and cycle life of the battery. At the same time, the addition of the chelating agent can also improve the solubility of the lithium salt and increase the conductivity of the electrolyte.

[0047] In summary, the electrolyte provided by the present invention has at least the following advantages:

[0048] 1) Improve the wettability and permeability of the electrolyte: The present invention adopts a multi-component compounding strategy and selects low-viscosity linear carbonate DMC and cyclic carbonate PC as the base solvents, which can effectively reduce the viscosity of the electrolyte and accelerate its penetration rate in the electrode pores. At the same time, the introduction of high dielectric constant EC enhances the solubility of lithium salts and improves ionic conductivity; high boiling point PA inhibits the volatilization of the electrolyte and improves high temperature performance. Under the synergistic effect of multiple solvents, not only a low system viscosity (2-8cP) is guaranteed, but also the high conductivity of the electrolyte (≥10ms / cm) is taken into account. In addition, the two fluorinated wetting agents PFSA and C2F5CONH (CH2CH2O) introduced 23 COC2F5 can significantly reduce the surface tension of the electrolyte. Among them, the perfluoroalkyl group in the PFSA molecule is lyophobic and easily enriched on the electrode surface to form a lyophobic coating; while the polyether segment is hydrophilic and easily forms hydrogen bonds with polar solvents to enhance the intermolecular force. The synergistic effect of the two greatly improves the wetting and spreading of the electrolyte on the electrode and the diaphragm, and accelerates the mass transfer process of the electrolyte in the porous electrode. The improvement of wettability is conducive to improving the utilization rate of the electrode, reducing the interface impedance, and improving the battery rate performance.

[0049] 2) Inhibit electrolyte decomposition and improve electrochemical performance: The present invention adopts a variety of functional additives for synergistic modification, among which VC and FEC are preferentially reduced and decomposed on the electrode surface to generate a stable SEI film, which protects the electrolyte from further reduction and decomposition, reduces charge consumption, and improves the initial coulombic efficiency. The SEI film can not only passivate the electrode active sites and inhibit continuous decomposition reactions, but also block solvent molecules from penetrating into the interior of the electrode, and slow down the stripping of the graphite negative electrode caused by solvent co-embedding. In addition, LiBOB and LiDFOB can also form a stable passivation film on the positive electrode surface, inhibit oxygen evolution reaction under high voltage, and slow down the oxidation decomposition of the positive electrode electrolyte. The dual protection of the negative electrode SEI film and the positive electrode passivation film significantly improves the electrochemical stability of the electrolyte and widens the voltage window. PS and DTD, as scavengers, can effectively complex trace amounts of HF and water in the electrolyte, further reducing the decomposition products of the electrolyte. BHT, as an antioxidant, can remove peroxides and free radicals in the electrolyte and delay the self-oxidation decomposition process of the electrolyte at high temperatures. The synergistic effect of multiple additives greatly improves the redox stability of the electrolyte, reduces irreversible capacity loss, and increases the cycle life of the battery.

[0050] 3) Improving the thermal stability and safety of the electrolyte: The present invention introduces flame retardant TTFP and chelating agent 18-crown ether-6, which can effectively improve the thermal stability and safety of the electrolyte. When the battery temperature rises sharply, the TTFP molecules are the first to undergo endothermic decomposition, taking away heat and delaying the further rise in the electrolyte temperature. At the same time, TTFP decomposes to release phosphate ions, which combine with free lithium ions in the electrolyte to form a high-temperature resistant Li3PO4 precipitate. The precipitate not only adsorbs on the surface of the diaphragm to form a physical barrier, blocking the direct contact between the positive and negative electrodes during thermal runaway, but also precipitates on the surface of the electrode to form a passivation protective layer, inhibiting the side reactions of the electrolyte and the electrode at high temperature, and preventing the further deterioration of thermal runaway. On the other hand, 18-crown ether-6 can effectively chelate free transition metal ions (such as Fe 2+ 、Ni 2+ The dual effects of flame retardants and chelating agents significantly increase the starting temperature of electrolyte decomposition and thermal runaway time, reduce the heat release during thermal runaway, and greatly improve the thermal stability and safety of the electrolyte.

[0051] According to the second aspect of the present application, the present invention also provides a method for preparing an electrolyte for a soft-pack cylindrical battery, comprising the following steps:

[0052] (1) Weigh each component according to the formula ratio;

[0053] (2) Mixing organic solvents DMC, PA, EC and PC at 20°C to 30°C and stirring at 500-1000 rpm for 10-30 min to fully mix them;

[0054] (3) adding functional additives VC, PS, DTD, FEC, LiBOB and LiDFOB to the mixed solvent in sequence, and continuing to stir under the above conditions for 30-60 minutes until the additives are completely dissolved;

[0055] (4) adding lithium salts LiPF6, LiFSI and LiPO2F2 to the above-mentioned mixed solution several times, stirring at 20°C to 30°C for 15-30 minutes after each addition until the lithium salt is completely dissolved;

[0056] (5) Degas the obtained electrolyte under a vacuum condition of -0.08 to -0.1 MPa for 2 to 4 hours to make the gas content in the electrolyte ≤50 ppm.

[0057] Among them, (1) the low temperature condition of 20-30℃ and nitrogen protection are used in the preparation process, which can minimize the contamination of O2 and H2O to the electrolyte, ensure the anhydrous and oxygen-free state of the electrolyte, and improve the consistency and stability of the product. (2) The step-by-step feeding and gradient dissolution method is adopted, the solvent and additives are first mixed evenly, and then the lithium salt is added in batches, which can avoid the local oversaturation crystallization of the lithium salt, accelerate the dissolution rate, and shorten the preparation cycle. (3) Under precisely controlled vacuum conditions (-0.08~-0.1MPa), long-term (2-4h) degassing can deeply remove the dissolved O2, CO2 and other gases in the electrolyte, so that the gas content is stably controlled below 50ppm; the fully degassed electrolyte can not only avoid the volatilization of the electrolyte during the use of the battery to generate bubbles, improve the capacity utilization of the battery, but also inhibit the side reactions induced by the gas and improve the cycle stability of the battery.

[0058] In summary, the electrolyte preparation process of the present invention adopts the method of step-by-step feeding and gradient dissolution to effectively avoid local supersaturation of lithium salts and additives, reduce the occurrence of crystallization, accelerate the dissolution rate, and shorten the preparation time; low temperature and inert atmosphere minimize the contamination of the electrolyte by moisture and oxygen, ensuring the stability of the electrolyte components; precise degassing process can deeply remove the dissolved gas in the electrolyte, increase the electrolyte filling volume, and prevent the generation of bubbles during the battery cycle, thereby improving the capacity utilization and safety performance of the battery. Therefore, the electrolyte preparation process optimized by the present invention is simple to operate, energy-saving and efficient, and the product quality is stable and controllable, which is very suitable for industrial production.

[0059] In one embodiment of the present application, the entire preparation process is carried out in an inert atmosphere with a moisture content of ≤0.1 ppm and an oxygen content of ≤0.1 ppm. Operating in an inert atmosphere with low moisture and oxygen content minimizes the impurity content in the electrolyte and improves the electrochemical performance of the battery.

[0060] The implementation and advantages of this application will be further explained below in conjunction with specific embodiments.

[0061] Example 1

[0062] The present embodiment provides an electrolyte for a soft-pack cylindrical battery, which is composed of the following parts by weight:

[0063] Lithium salt: 14 parts of lithium hexafluorophosphate (LiPF6), 3.5 parts of lithium bis(fluorosulfonyl)imide (LiFSI), 0.5 parts of lithium difluorophosphate (LiPO2F2); wherein the total content of lithium salt is 18 parts.

[0064] Organic solvent: 15 parts of ethylene carbonate (DMC), 35 parts of propyl propionate (PA), 15 parts of ethylene carbonate (EC), 8 parts of propylene carbonate (PC); wherein the total content of the organic solvent is 73 parts.

[0065] Functional additives: 1 part of vinylene carbonate (VC), 1.6 parts of propylene sulfite (PS), 5 parts of diethylene sulfate (DTD), 1 part of fluoroethylene carbonate (FEC), 0.2 parts of lithium bis(oxalatoborate) (LiBOB), and 0.2 parts of lithium bis(fluorooxalatoborate) (LiDFOB); wherein the total amount of the functional additives is 9 parts.

[0066] The preparation method of the electrolyte for the soft-pack cylindrical battery is as follows:

[0067] (1) Weigh each component according to the formula ratio;

[0068] (2) Mix the organic solvents DMC, PA, EC and PC at 25°C and stir at 800 rpm for 20 min to ensure that they are fully mixed;

[0069] (3) adding functional additives VC, PS, DTD, FEC, LiBOB and LiDFOB to the mixed solvent in sequence, and continuing to stir under the above conditions for 45 min until the additives are completely dissolved;

[0070] (4) adding lithium salts LiPF6, LiFSI and LiPO2F2 to the above mixture several times, stirring at 25°C for 15-30 minutes after each addition until the lithium salt is completely dissolved;

[0071] (5) The obtained electrolyte was degassed under a vacuum condition of -0.1 MPa for 3 h to make the gas content in the electrolyte ≤50 ppm.

[0072] The entire preparation process should be carried out in a dry inert atmosphere with a moisture content of ≤0.1 ppm and an oxygen content of ≤0.1 ppm to prevent hydrolysis and oxidation.

[0073] The viscosity of the electrolyte is 5 cP, and the conductivity of the electrolyte at room temperature is 12.5 mS / cm.

[0074] Example 2

[0075] The difference from Example 1 is that this example adds 0.2 parts by weight of PFSA on the basis of Example 1.

[0076] The rest is the same as in Example 1 and will not be described again here.

[0077] Example 3

[0078] The difference from Example 1 is that this example increases the weight of C2F5CONH(CH2CH2O) by 0.2 parts on the basis of Example 1. 23 COC2F5.

[0079] The rest is the same as in Example 1 and will not be described again here.

[0080] Example 4

[0081] The difference from Example 1 is that this example adds 0.2 parts by weight of PFSA and 0.2 parts by weight of C2F5CONH(CH2CH2O) on the basis of Example 1. 23 COC2F5.

[0082] The rest is the same as in Example 1 and will not be described again here.

[0083] Example 5

[0084] The difference from Example 1 is that this example adds 0.3 parts by weight of BHT on the basis of Example 1.

[0085] The rest is the same as in Example 1 and will not be described again here.

[0086] Example 6

[0087] The difference from Example 1 is that this example adds 0.8 parts by weight of TTFP based on Example 1.

[0088] The rest is the same as in Example 1 and will not be described again here.

[0089] Example 7

[0090] The difference from Example 1 is that this example adds 0.3 parts by weight of 18-crown ether-6 based on Example 1.

[0091] The rest is the same as in Example 1 and will not be described again here.

[0092] Comparative Example 1

[0093] Different from the embodiment, the lithium salt in the electrolyte of this comparative example is only LiPF6, the organic solvent is EC+DMC+PC (weight ratio 1:1:1), and the additive is VC+FEC (weight ratio 1:1).

[0094] The rest is the same as in Example 1 and will not be described again here.

[0095] The electrolytes prepared in the above-mentioned embodiments and comparative examples were respectively matched with winding cores to prepare soft-pack cylindrical lithium-ion batteries, wherein the winding cores were wound with positive electrode sheets made of NCM811 positive electrode materials, negative electrode sheets made of graphite negative electrode materials and PE separators.

[0096] The following electrochemical performance tests were performed on the electrolytes and lithium-ion batteries prepared in the examples and comparative examples, respectively. The test results are shown in Table 1 below.

[0097] (1) Wetting angle test: Drop the electrolyte on the surface of the PP diaphragm and measure its wetting angle with a contact angle meter. The smaller the angle, the better the wettability.

[0098] (2) Conductivity test: The ionic conductivity of the electrolyte was measured at 25°C using a conductivity meter.

[0099] (3) First coulombic efficiency test: A half-cell with lithium carbonate negative electrode / metal lithium positive electrode was charged and discharged at a rate of 0.1C, and the coulombic efficiency of the first charge and discharge was calculated.

[0100] (4) Cyclic performance test: A full battery with NCM811 positive electrode / silicon carbon negative electrode was charged and discharged 500 times at a 1C rate at 25°C, and the capacity retention rate was recorded.

[0101] (5) Rate performance test: Charge and discharge at 0.2C, 0.5C, 1C, 2C and 3C rates at 25°C, and record the discharge capacity at different rates.

[0102] (6) High temperature storage performance: After the battery is stored in a 60°C high temperature box for 30 days, its capacity retention rate is tested.

[0103] (7) Thermal runaway test: The ARC thermal runaway test is used to record the battery's thermal runaway starting temperature and maximum temperature rise rate.

[0104] Table 1

[0105]

[0106]

[0107] The test results of Table 1 above are analyzed as follows:

[0108] (1) By comparing Example 1 with Comparative Example 1, it can be seen that after the solvent and the multifunctional additive of the present invention are compounded, the viscosity and wetting angle of the electrolyte are significantly reduced, the conductivity is greatly improved, and the first coulombic efficiency, cycle capacity retention rate, rate performance and high-temperature storage performance are significantly improved, indicating that the electrolyte of the present invention not only improves the wettability, but also inhibits the side reaction, thereby improving the electrochemical performance and high-temperature performance.

[0109] (2) Comparing Example 1 with Examples 2-4, introducing a wetting agent PFSA or C2F5CONH(CH2CH2O) 23 After COC2F5, the wetting angle is further reduced, the conductivity is slightly improved, and other properties are also improved to varying degrees, indicating that both wetting agents can improve the wettability of the electrolyte. When the two wetting agents are used in combination (Example 4), the wettability is improved most significantly, and other properties are also better than a single wetting agent, indicating that the two have a synergistic effect.

[0110] (3) Comparing Example 1 with Examples 5-7, after adding BHT, TTFP and 18-crown ether-6, the high temperature storage performance, thermal stability and cycle performance are all improved. Among them, BHT has the most significant improvement on high temperature storage performance; TTFP can greatly increase the thermal runaway temperature and reduce the risk of thermal runaway; 18-crown ether-6 improves the conductivity while improving the cycle performance most significantly.

[0111] It should be noted that the contents not described in detail in this specification belong to the prior art known to professional and technical personnel in the field and will not be repeated here.

[0112] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. An electrolyte for a soft-pack cylindrical battery, characterized in that: The invention comprises the following components in parts by weight: 10-25 parts of lithium salt, 60-85 parts of organic solvent and 5-15 parts of functional additive; The lithium salt includes 10-18 parts of lithium hexafluorophosphate (LiPF6), 2-5 parts of lithium bis(fluorosulfonyl)imide (LiFSI) and 0.1-1 parts of lithium difluorophosphate (LiPO2F2); The organic solvent comprises 10-20 parts of ethylene carbonate (DMC), 30-45 parts of propyl propionate (PA), 10-20 parts of ethylene carbonate (EC) and 5-10 parts of propylene carbonate (PC); The functional additives include 0.5-2 parts of vinylene carbonate (VC), 1-3 parts of propylene sulfite (PS), 3-8 parts of diethylene sulfate (DTD), 0.5-1.5 parts of fluoroethylene carbonate (FEC), 0.1-0.5 parts of lithium bis(oxalatoborate) (LiBOB) and 0.1-0.5 parts of lithium bis(fluorooxalatoborate) (LiDFOB).

2. The electrolyte for soft-pack cylindrical batteries according to claim 1, characterized in that: The viscosity of the electrolyte is 2-8 cP, and the conductivity of the electrolyte at room temperature is ≥10 mS / cm.

3. The electrolyte for soft-pack cylindrical batteries according to claim 1, characterized in that: The electrolyte also includes 0.1-0.5 parts of a wetting agent, ammonium perfluorooctane sulfonate.

4. The electrolyte for soft-pack cylindrical batteries according to claim 1 or 3, characterized in that: The electrolyte also includes a wetting agent C2F5CONH(CH2CH2O) 23 COC2F5 0.1-0.5 parts.

5. The electrolyte for soft-pack cylindrical batteries according to claim 1, characterized in that: The electrolyte also includes 0.1-0.5 parts of antioxidant 2,6-di-tert-butyl-4-methylphenol.

6. The electrolyte for soft-pack cylindrical batteries according to claim 1, characterized in that: The electrolyte also includes 0.5-1 part of flame retardant tris(2,2,2-trifluoroethyl)phosphate.

7. The electrolyte for soft-pack cylindrical batteries according to claim 1, characterized in that: The electrolyte also includes 0.1-1 part of chelating additive 18-crown ether-6.

8. A method for preparing an electrolyte for a soft-package cylindrical battery according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weigh each component according to the formula ratio; (2) mixing organic solvents of ethylene carbonate (DMC), propyl propionate (PA), ethylene carbonate (EC) and propylene carbonate (PC) at 20° C. to 30° C. and stirring at a speed of 500 to 1000 rpm for 10 to 30 min to fully mix them; (3) adding functional additives vinylene carbonate (VC), propylene sulfite (PS), diethylene sulfate (DTD), fluoroethylene carbonate (FEC), lithium bis(oxalatoborate) (LiBOB) and lithium bis(fluorooxalatoborate) (LiDFOB) to the mixed solvent in sequence, and continuing to stir under the above conditions for 30-60 minutes until the additives are completely dissolved; (4) adding lithium salts of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium difluorophosphate (LiPO2F2) to the mixed solution in multiple times, stirring at 20°C to 30°C for 15-30 minutes after each addition until the lithium salt is completely dissolved; (5) Degas the obtained electrolyte under a vacuum condition of -0.08 to -0.1 MPa for 2 to 4 hours to make the gas content in the electrolyte ≤50 ppm.

9. The method for preparing an electrolyte for a soft-pack cylindrical battery according to claim 8, characterized in that: The entire preparation process is carried out in an inert atmosphere with moisture ≤ 0.1 ppm and oxygen ≤ 0.1 ppm.

Citation Information

Patent Citations

  • Functional additive for electrolyte, long-circulation electrolyte of lithium ion battery and lithium ion battery

    CN106129456A

  • Lithium battery electrolyte and lithium battery

    CN112803072A

  • High-wettability electrolyte for cylindrical lithium ion battery

    CN113488696A

  • Electrolyte for high-power lithium ion battery

    CN117712489A

  • Electrolyte solution comprising pyrosulfate-boron trifluoride composite lithium salt, and lithium-ion secondary battery

    WO2024120338A1

Cited By

  • Electrolyte for aluminum electrolytic capacitor and preparation method thereof

    CN120637108A